An ancestral interaction module promotes oligomerization in divergent mitochondrial ATP synthases - Gahura, Ondřej; Mühleip, Alexander; Hierro-Yap, Carolina; Panicucci, Brian; Jain, Minal; Hollaus, David; Slapničková, Martina; Zíková, Alena; Amunts, Alexey (Nature communications, 2022)
Mitochondrial ATP synthase forms stable dimers arranged into oligomeric assemblies that generate the inner-membrane curvature essential for efficient energy conversion. Here, we report cryo-EM structures of the intact ATP synthase dimer from Trypanosoma brucei in ten different rotational states. The model consists of 25 subunits, including nine lineage-specific, as well as 36 lipids. The rotary mechanism is influenced by the divergent peripheral stalk, conferring a greater conformational flexibility. Proton transfer in the lumenal half-channel occurs via a chain of five ordered water molecules. The dimerization interface is formed by subunit-g that is critical for interactions but not for the catalytic activity. Although overall dimer architecture varies among eukaryotes, we find that subunit-g together with subunit-e form an ancestral oligomerization motif, which is shared between the trypanosomal and mammalian lineages. Therefore, our data defines the subunit-g/e module as a structural component determining ATP synthase oligomeric assemblies.
Keywords: Protein Subunits; Lipids; mitochondriální protonové ATPasy; Animals; podjednotky proteinů; Protons; lipidy; zvířata; Mammals; Water; savci; Mitochondrial Proton-Translocating ATPases; voda; protony